Comparative study of primary closure versus non-closure of animal bite injuries in head and neck region: case study of 540 patients - Saple, Pallavi; Chavan, Shrinivas S.; Kale, Vitthal Dada; Kurle, Vinayak; Khond, Abhishek (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Rabies is a zoonotic disease caused by lyssavirus and spread through saliva of rabid animal bite. This study was taken to compare primary closure versus non-closure of animal bite wounds. Methods: This is a prospective randomized study. Patients were divided into 2 groups. Group A consisted of patients with non-closure of wounds and group B with primary closure of wounds. Patients were followed up for wound healing time, infection and cosmesis. Results: This study consists of 540 patients (323 males and 217 females). The common age group was paediatric and geriatric age. Most common animal bite was from dogs. The average healing time in non-infected wound in group A versus group B with Lackman’s I and II grading was 10.5±1.25 and 12.5±1.5 days versus 7±1.25 and 8.5±1.5 days respectively. There were 19 cases in group A and 17 cases in group B with infection which subsided with antibiotics in 24 hrs. Cosmesis graded on VSS was better in group B (average 4.03±1.5) as compared to group A (average 2.44±0.185). Only one patient from group A with Lackman’s grade II contacted rabies died 2yrs after the bite. Conclusions: Animal bite wounds over head and neck were found to be more common in paediatric and geriatric population who are more vulnerable. Infection and spread of rabies virus through these wounds can be prevented by thorough debridement and cleaning whereas primary suturing helps in achieving early wound healing and better cosmesis producing a socially and functionally acceptable scar.